The Role of Religious and Ethical Values in Preventing the Influence of LGBT Among Adolescents at State Vocational School 1 Cikampek - Salma Gania; Ratu Nikita Ristanti; Ahmad Farhan Mulyadi; Oyoh Bariah (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to analyze the role of religious values in shaping adolescents' character in facing negative influences, particularly LGBT, in both the school and family environments. The methods used in this research include in-depth interviews with Mr. Wawan Iwank Kurniawan, an Islamic Religious Education teacher at SMKN 1 Cikampek, and direct socialization to students in the classroom to enhance their understanding of the importance of religious values in dealing with such social issues. The findings indicate that religious values such as faith, worship, and morality play a crucial role in shaping adolescents' character. Parents, as the "first madrasa," play a primary role in instilling religious values from an early age, while schools contribute by reinforcing religious understanding through humanistic and relevant teaching. Although most parents at SMKN 1 Cikampek are aware of the importance of religious education at home, challenges in optimizing their role still exist. The collaboration between parents and schools has proven effective in strengthening students' character and countering negative influences such as LGBT.